Moment redistribution in reinforced concrete beams and one-way slabs using 500 MPa steel - Islam, Mohammad M. (Curtin University, 2002)
In the Australian Standard, AS 3600-2001, the neutral axis parameter Ku is used as a convenient, but approximate, parameter to design for moment redistribution in building frames. The research work reported herein was conducted to obtain complete information regarding moment redistribution of beams and one-way slabs using 500 MPa steel reinforcement.A computer based iterative numerical method was developed to analyse reinforced two-span continuous concrete beams and one-way slabs. The method takes into account the material and geometrical non-linearities in the calculations. The deflected shape of the beam and one-way slab was calculated by dividing the span length into a number of rigid segments. The program also calculates the failure load and extent of moment redistribution. The analytical method was verified against the test results reported in the literature. The analytical results for load-deflection graphs and moment redistribution showed a good agreement with the test results.A parametric study was conducted using analytical method. The results of this study showed that moment redistribution depends not only on the neutral axis parameter (Ku) but also on the ratio of neutral axis parameter (Ku-/Ku+), ultimate steel strain (ªsu) and concrete compressive strength (fc).